1999
DOI: 10.1163/156853999501739
|View full text |Cite
|
Sign up to set email alerts
|

Social Bonds and Genetic Ties: Kinship, Association and Affiliation in a Community of Bonobos (Pan Paniscus)

Abstract: SummaryStudies of captive populations of bonobos suggest that females are more gregarious than males. This seems to contradict assumed sex-differences in kinship deriving from a speciestypical dispersal pattern of female exogamy and male philopatry. Here we present data on spatial associations and af liative relations among members of one wild community (Eyengo) for which genetic relationships were identi ed by analysing mitochondrial and nuclear DNA. Our data from Lomako con rm the existence of spatial associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 43 publications
2
33
1
Order By: Relevance
“…This confirms the findings for wild bonobos at Lomako Hohmann et al 1999;Hohmann and Fruth 2002). In two groups, we found a tendency for females to associate preferably with other females, but grooming was not more pronounced between these females.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This confirms the findings for wild bonobos at Lomako Hohmann et al 1999;Hohmann and Fruth 2002). In two groups, we found a tendency for females to associate preferably with other females, but grooming was not more pronounced between these females.…”
Section: Discussionsupporting
confidence: 90%
“…However, it has been stated that this tendency of female bonding in bonobos may be a side effect of captivity (Stanford 1998;Franz 1999;Hohmann et al 1999), similar to the stronger female bonding of captive chimpanzees (de Waal 1994;Baker and Smuts 1994). Although female-female relations are indeed well developed in wild bonobos, several studies found that intersexual bonds are stronger (Kuroda 1979(Kuroda , 1980Kano 1982;Furuichi and Ihobe 1994;Muroyama and Sugiyama 1994;Hohmann et al 1999).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations